A pictorial key to important Diaspididae (Hemiptera: Coccoidea) of the world (Bollettino di zoologia agraria e bachicoltura, 2024)
A pictorial key to 48 genera and 100 species of Diaspididae (Hemiptera: Coccoidea) of economic or quarantine importance worldwide has been compiled, using Linnaeus II software developed by the Expert Center for Taxonomic ldentification (ETI). The CD-ROM will provide information on each species (diagnosis, synonymy, taxonomy, host range, symptoms of infestation, distribution, biology and ecology, economic impact, detection and natural enemies, separation from similar species, and literature, according to the information available). There are also modules on: Methods (collection, preservation, preparation and storage), Host Plants and Higher Taxa. A hyper-linked Glossary and an Index to both Latin and common names is also provided. The CD-ROM is part of the series 'Arthropods of Economic Importance', a project of the Zoological Museum, University of Amsterdam. ETI, the Natural History Museum (London) and CAB International are some of the collaborators in the project. The CD-ROM will be published by ETI (http://www.eti.uva.nl) and should be available from bookstores by the summer of 2002.
Keywords: Diaspididae; pests; identification; datasheets; host plants; methods